O programa ANDIFES de mobilidade acadêmica: uma mobilidade estudantil no sistema federal de ensino superior brasileiro - Raquel Leite Braz (2015)
The academic mobility constitutes an important element for higher education since its inception. Throughout the globalization process, education policies for internationalization of education were intensified, increasing the academic temporary migration of college students. In the Brazilian Higher Education, consisting of a complex and diverse system of public and private institutions with different types of courses and programs, there are modalities for national and international academic mobility. In 2003, he was created by the National Association of Directors of Higher Education Federal Institutions (Andifes) a student mobility program to be held exclusively in Brazilian territory. The Andifes Academic Mobility Program (PAMA) is performed by means of an agreement between the Association and 63 Federal Institutions of higher education (IFES), establishing a relationship of reciprocity between the signatory for mobility of undergraduate students, so that they can attend the curriculum components in different federal institution that they are regularly enrolled. In this study, we sought to identify the sociodemographic profile of the student participants of the program, as well as know their motivations for participation in a national mobility, considering the internationalization of education and the growth of international mobility. The methodology involved a documentary research, the application of a virtual questionnaire, the semi-structured interviews and the case study of the participants of the Federal University of Ouro Preto (UFOP). Data analysis showed that participating students PAMA are mostly white, female, with a mean age of 23 years, from small families, with fewer siblings, parents with a high school education or higher education, and income range of up to 10 minimum wages. Largely, they are students of daytime undergraduate courses, the area of Social and Applied Sciences, universities located in the southeast region and school careers without major interruptions. As the main motivation to participate in the Program, the students pointed out the learning and experiences provided by this experience. The participants evaluated as deficient divulgation and information about PAMA, the IFES, and complained of the difficulties to complement, in academic transcript, the routed credits during the academic mobility. In this study, came to the conclusion that, on any scale that takes place, the mobility is a constructive experience in the formation of higher education students and that it should be expanded to reach different student profiles.